2021
DOI: 10.1021/acs.macromol.0c02208
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Melt Crystallization of Bisphenol-A Polycarbonate Jointly Induced by Pressure and Flow

Abstract: Bisphenol-A polycarbonate (PC) is an intrinsically crystallizable polymer. Its industrial parts, however, invariably remain in an amorphous state due to its extremely slow crystallization kinetics. In the current study, we reported rapid melt crystallization of bulk PC jointly induced by pressure and shear flow. The crystallinity of pure bulk PC reached up to ∼25% when crystallized at 100 MPa and 42.8 s −1 for only 60 min, ca. 500 times faster than quiescent melt crystallization under ordinary pressure. In con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 64 publications
0
23
0
Order By: Relevance
“…The PC crystallization, which is usually a remarkably slow process, may be accelerated at the high process temperature and through the presence of CB, as also observed in the presence of carbon fillers (CB, vapor grown carbon fibers, carbon nanotubes, carbon fibers) [2,42]. Finally, the relatively high pressure of the extrusion in conjunction with the high shear stress of the injection molding process could stimulate, to some extent, the formation of a very small degree of crystallinity that under normal process conditions is nearly completely amorphous [43,44]. However, the observed crystallization effect does not result in noticeable changes in the DSC profiles.…”
Section: Sem Analysismentioning
confidence: 98%
“…The PC crystallization, which is usually a remarkably slow process, may be accelerated at the high process temperature and through the presence of CB, as also observed in the presence of carbon fillers (CB, vapor grown carbon fibers, carbon nanotubes, carbon fibers) [2,42]. Finally, the relatively high pressure of the extrusion in conjunction with the high shear stress of the injection molding process could stimulate, to some extent, the formation of a very small degree of crystallinity that under normal process conditions is nearly completely amorphous [43,44]. However, the observed crystallization effect does not result in noticeable changes in the DSC profiles.…”
Section: Sem Analysismentioning
confidence: 98%
“…As shown in Figure 6, the XRD curve of neat PC film (0%) displayed a broad halo with low intensity at 17.4°, attributed to the (020) crystal plane in the monoclinic form of PC 36,37 . It was reported that PC could form a crystalline structure by solvent casting and evaporation 38,39 . Meanwhile, Figure 6 showed that the XRD curves of all the PAL‐CNC/PC nanocomposite films presented a sharp and well‐defined reflection at about 17.4°.…”
Section: Resultsmentioning
confidence: 93%
“…36,37 It was reported that PC could form a crystalline structure by solvent casting and evaporation. 38,39 Meanwhile, Figure 6 showed that the XRD curves of all the PAL-CNC/PC nanocomposite films presented a sharp and well-defined reflection at about 17.4 . In addition, the intensity of the reflection at 17.4 was greater for the PC nanocomposite films than for the pure PC film, indicating more crystalline domain was formed after the addition of the PAL-CNCs.…”
Section: Xrd Of the Nanocomposite Filmsmentioning
confidence: 99%
“…In recent years, through the combination of homemade equipment and high time and spatial resolution experimental techniques, some research groups have conducted research on FIC in complex processing environments and achieved some interesting results. [35][36][37][38][39][40] This review attempts to present the recent efforts on FIC under simple flow conditions to clarify the fundamental mechanism and under complex flow conditions to mimic real polymer processing. We mainly summarize the studies in the last 5 years.…”
Section: Introductionmentioning
confidence: 99%